Either with us or against us? Third-country alignment with EU sanctions against Russia/Ukraine. Issue 3 (2nd July 2016) - Hellquist, Elin
Abstract: Since the mid-1990s, selected neighbours have in impressive numbers aligned with European Union (EU) foreign policy sanctions. However, much more than for any other sanctions case, neighbours have declined joining recent measures against Russia/Ukraine. This article uses freshly gathered data from the entire period of the Common Foreign and Security Policy (CFSP) to analyse how the practice of alignment influences international relations in Europe. Thereby, the article demonstrates that: (1) sanctions are not a two-party game, but an instrument that impacts broadly on relations with third countries; (2) alignment with sanctions not only articulates similarity, but contributes to normative polarization in wider Europe; (3) for a high-salience case such as Russia sanctions, neighbours are reluctant to be instrumentalized for EU foreign policy purposes .